Peranan Orang Tua dalam Pembentuk Moral Anak - Jeni Nopilana (Indonesian Journal of Elementary and Childhood Education, 2025)
The life of every human being must go through a period of development which includes social, cognitive, interest and moral aspects, starting from infancy, childhood, adolescence and old age. Along with this development, the role of the family environment greatly determines whether or not a child reaches this stage of development. Because the family is the first and foremost education for children, especially in forming the basics of their personality. This research examines "the role of parents in shaping children's morals". This research is library research, data analysis was carried out using content analysis, which covers three aspects of moral development, namely moral views, moral feelings and moral behavior. From the research results, it was concluded that the role of parents in developing children's morals is first by introducing the moral values that apply in society and involving children in a discussion of moral dilemmas. The two roles of parents in developing moral feelings are by instilling a loving attitude, arousing feelings of guilt, implementing disciplinary parenting and strengthening conscience. Meanwhile, the third role of parents in developing children's moral behavior is by strengthening altruistic behavior, providing models and implementing discipline.